Solar Photocatalytic Degradation of Bisphenol A on Immobilized ZnO or TiO2 - Andreas Zacharakis; Efthalia Chatzisymeon; Vassilios Binas; Zacharias Frontistis; Danae Venieri; Dionissios Mantzavinos (International Journal of Photoenergy)
The removal of bisphenol A (BPA) under simulated solar irradiation and in the presence of either TiO2 or ZnO catalysts immobilized onto glass plates was investigated. The effect of various operating conditions on degradation was assessed including the amount of the immobilized catalyst (36.1–150.7 mg/cm2 for TiO2 and 0.5–6.8 mg/cm2 for ZnO), initial BPA concentration (50–200 μg/L), treatment time (up to 90 min), water matrix (wastewater, drinking water, and pure water), the addition of H2O2 (25–100 mg/L), and the presence of other endocrine disruptors in the reaction mixture. Specifically, it was observed that increasing the amount of immobilized catalyst increases BPA conversion and so does the addition of H2O2 up to 100 mg/L. Moreover, BPA degradation follows first-order reaction kinetics indicating that the final removal is not practically affected by the initial BPA concentration. Degradation in wastewater is slower than that in pure water up to five times, implying the scavenging behavior of effluent’s constituents against hydroxyl radicals. Finally, the presence of other endocrine disruptors, such as 17α-ethynylestradiol, spiked in the reaction mixture at low concentrations usually found in environmental samples (i.e., 100 μg/L), neither affects BPA degradation nor alters its kinetics to a considerable extent.